A metabolic profiling approach to an Italian sage leaf extract (SoA541) defines its antioxidant and anti-acetylcholinesterase properties. (February 2017) - Pacifico, Severina; Piccolella, Simona; Lettieri, Annamaria; Nocera, Paola; Bollino, Flavia; Catauro, Michelina
Highlights: SoA541 was a phenolic enriched extract from leaves of cultivated sage plants. It was quali- and quantitatively analyzed through LC-ESI-MS/MS techniques. SoA541 originally contained lignin oligomers, beyond other known constituents. The extract showed anti-lipoperoxidant, antioxidant and anti-AChE properties. Abstract: LC-MS/MS techniques were applied to analyze, quali- and quantitatively, a phenol extract from leaves of Salvia officinalis, cultivated in the Campania Region (Italy). It accounted for ∼50% of abietane diterpenes, ∼40% of phenylpropanoid constituents, and 10% flavonoids, and so called SoA541. Lignin oligomers were detected for the first time as sage constituents. SoA541 exerted anti-lipoperoxidative and antioxidant properties at dose levels <125 μg/mL on SH-SY5Y cells, and its ability to inhibit the AChE enzyme was far greater than donepezil. The anti-AChE effectiveness was dose-dependent up to a maximum (62.5 μg/mL), beyond which the effect decreased. The data obtained encourage further research aimed at evaluating a potential use of the "Campania" sage in the prevention of CNS diseases in animal models.